A Study On Consumer Satisfaction On Masqati Dairy Products - Varsha Bikkumalla; Bhanwal Krish; Zaker Ul Oman (PT Agung Media Publisher, 2024)
This study aims to determine customer satisfaction levels with Masqati Dairy Products, a supreme dairy brand in India. The research emphasizes identifying the factors affecting customer satisfaction, including product quality, packaging, pricing, and distribution, and enhancing them. To determine how masqati dairy products are different from other dairy products. A mixed-methods approach was used to gather data. The data would be analyzed and interpreted using statistical techniques such as descriptive statistics. The finding could indicate that product quality, packaging, and pricing are the most significant factors affecting customer satisfaction, and identify the areas for improvement within masqati dairy products while distribution had little impact. The study would conclude with recommendations for Masqati Dairy Products to enhance its customer satisfaction and loyalty by improving its product quality, packaging, and product strategies. This can guide strategic decisions to upgrade or improve customer satisfaction, loyalty, trust and thereby strengthening Masqati Dairy’s market position.